Intraoperative hemodynamic optimization using the hypotension prediction index vs. goal-directed hemodynamic therapy during elective major abdominal surgery: the Predict-H multicenter randomized controlled trial - Lorente, Juan V.; Ripollés-Melchor, Javier; Jiménez, Ignacio; Becerra, Alejandra I.; Mojarro, Irene; Fernández-Valdes-Bango, Paula; Fuentes, Maria A.; Moreno, Ana; Agudelo, Maria E.; Villar-Pellit de la Vega, Angel; Ruiz-Escobar, Alicia; Cortés, Azahara; et al. (Frontiers in Anesthesiology, 2023)
Background: Intraoperative hypotension (IOH) is associated with increased morbidity and mortality after major abdominal surgery but remains significant even using goal-directed hemodynamic therapy (GDHT) protocols. The Hypotension Prediction Index (HPI) is a machine learning-derived parameter that predicts arterial hypotension. We tested the hypothesis that an HPI-based protocol reduces the duration and severity of hypotension compared to a GDHT protocol during major abdominal surgery. Methods: This is a parallel-arm, double-blinded, multi-center randomized trial involved adult patients undergoing elective major abdominal surgery at five centers. Patients were optimized according to a previously recommended GDHT protocol (GDHT group) or the HPI value (HPI group). Hemodynamic optimization in both groups started 15 minutes after the surgical incision. The primary outcome was the intraoperative time-weighted average of mean arterial pressure under 65 mmHg (TWA-MAP<65 mmHg). Other metrics for IOH and secondary outcomes, including TWA below individual baseline values of intraoperative tissue oxygenation (StO2), postoperative AKIRisk, postoperative complications, length of stay, and 30-day mortality were explored. Results: Eighty patients were randomized (40 patients in each group). TWA-MAP<65 mmHg was 0.06 (25th to 75th interquartile range: 0 to 0.27) mmHg in the GDTH group vs 0 (0 to 0.04) mmHg in the HPI group (p=0.015). Total time with MAP<65 mmHg per patient was 4.6 (0 to 21) minutes in GDHT and 0 (0 to 3) minutes in the HPI group (p=0.008). The TWA below the baseline StO2 was 0.40 (0.12 to 2.41) % in GDHT and 0.95 (0.15 to 3.20) % in HPI group (p=0.353). AKIRisk values obtained in GDHT was 0.30 (0.14 to 0.53) and 0.34 (0.15 to 0.67) in the HPI group (p= 0.731). Both groups had similar postoperative complications, length of stay, and 30-day mortality. Conclusions: An HPI-based protocol reduced intraoperative hypotension compared to a standard GDHT protocol, with no differences in tissue oxygenation and postoperative AKIRisk.